PERANAN ORANG TUA DALAM MENUNJANG TINGKAT PENDIDIKAN ANAK PADA MASA PANDEMI COVID 19 DI DESA SAOLAT KECAMATAN WASILE SELATAN KABUPATEN HALMAHERA TIMUR - Bahi, Tirsa; Tasik, Femmy C. M.; Mumu, Rudy (HOLISTIK, Journal Of Social and Culture, 2021)
Countries in the world are currently facing the Covid-19 pandemic, including Indonesia the Covid-19 pandemic becomes a major crisis, people are force to quit their daily routines and ask to stay at home. The spread of coronavirus in various countries makes major changes, such as the field of economics, technology and no exception in the field of Education.The home learning policy resulted in learning having to be done online. They cannot come face to face, because for the prevention of covid-19 transmission. Online learning was developed to expand the reach and increase the availability of Education services. Although it looks fun, it turns out that online learning conducted from home is not easy. During learning from home, students get a lot of work. Not to mention, the role of parents who have to supervise their child is learning process while at home.The role of parents in supporting the level of education of children during the Covid-19 Pandemic. For the role of parents in Saolat Village is still very lacking because judging from the education of parents, some parents in Saolat Village are educated and there are some parents do not have an education so parents do not understand about the education of children with the current situation. But there are also some parents who pay attention to children's learning and try to make the child learn comfortably by accompanying when the child learns. Lack of internet access so that children cannot learn online, this is because there are limited facilities in the form of mobile phones and children is learning manuals.Keywords: pandemic covid-19, education, parents